2016
DOI: 10.1088/1361-6560/61/24/8736
|View full text |Cite
|
Sign up to set email alerts
|

Stability of radiomic features in CT perfusion maps

Abstract: This study aimed to identify a set of stable radiomic parameters in CT perfusion (CTP) maps with respect to CTP calculation factors and image discretization, as an input for future prognostic models for local tumor response to chemo-radiotherapy. Pre-treatment CTP images of eleven patients with oropharyngeal carcinoma and eleven patients with non-small cell lung cancer (NSCLC) were analyzed. 315 radiomic parameters were studied per perfusion map (blood volume, blood flow and mean transit time). Radiomics robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…Published studies show promising results in NSCLC treatments, yet there are still major challenges and limitations to resolve before they can be translated into reliable clinical application. A number of experimental clinical studies have found that current restrictions of radiomics in its therapeutic application are mainly subjected to (1) image standardization, 29 , 91 (2) image registration, 92 - 94 and (3) data sharing. 5 The on-going research activities focusing on tackling these limitations are elaborated subsequently.…”
Section: Current Research Challenges and Prospectsmentioning
confidence: 99%
“…Published studies show promising results in NSCLC treatments, yet there are still major challenges and limitations to resolve before they can be translated into reliable clinical application. A number of experimental clinical studies have found that current restrictions of radiomics in its therapeutic application are mainly subjected to (1) image standardization, 29 , 91 (2) image registration, 92 - 94 and (3) data sharing. 5 The on-going research activities focusing on tackling these limitations are elaborated subsequently.…”
Section: Current Research Challenges and Prospectsmentioning
confidence: 99%
“…38 In the single study that focused on the acquisition parameters at risk of influencing perfusion maps, Bogowicz et al found that the percentage of unstable texture features ranged from 56-98% with different artery contouring, and from 58-75% with different temporal resolution, which is higher than in our study. 27 This highest variability in their study may be explained by the difference in histological types, in imaging modality (CT vs. MRI), in the texture features that were calculated, and in the perfusion maps that were studied (blood flow, mean time transit, and blood volume vs. AUC and K trans in our studies).…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies have demonstrated that temporal parameters (ie, scan duration and temporal resolution) could significantly modify the ability to discriminate benign from malignant prostate or breast lesions, but they were based on average values of DCE‐MRI indices or morphology of the time–intensity curves. Only one study has focused on the stability of texture features extracted from computed tomography (CT) perfusion maps identifying an influence of temporal resolution . Hence, data regarding the influence of temporal parameters on texture features extracted from DCE‐MRI parametric maps are lacking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of image processing and of feature extraction algorithms and implementation on the feature variation is tackled by the Image Biomarker Standardization Initiative (IBSI) [16]. Various studies have evaluated the reproducibility and stability of texture features and the influence of scanner variation and reconstruction settings [5,6,8,14,[17][18][19][20]. These studies generally aim at selecting stable and repeatable texture features for a given task with test-retest and inter-rater reliability analysis, without proposing a method to standardize unstable features.…”
Section: Introductionmentioning
confidence: 99%